Cover Picture: Efficient Vanadium‐Catalyzed Aerobic C−C Bond Oxidative Cleavage of Vicinal Diols (Adv. Synth. Catal. 17/2018). Issue 17 (2nd September 2018) - Amadio, Emanuele; González‐Fabra, Joan; Carraro, Davide; Denis, William; Gjoka, Blerina; Zonta, Cristiano; Bartik, Kristin; Cavani, Fabrizio; Solmi, Stefania; Bo, Carles; Licini, Giulia
Abstract : Theinside cover picture, provided by Giulia Licini, Carles Bo and coworkers illustrates the highly chemoselective aerobic oxidative cleavage of 1, 2‐diols to the corresponding carbonyl derivatives catalyzed by vanadium‐aminotriphenolate complexes. This catalytic method works with a large variety of glycols, linear or cyclic, with aromatic or aliphatic substituents. Pre‐association of the substrate to the metal center, followed by a two‐electron oxidation mechanism, yields the carbonyl derivatives and a reduced V III metal complex, which is rapidly oxidized back to the catalyst by O2 . Details of this work can be found in the full paper on pages 3281–3291 (E. Amadio, J. González‐Fabra, D. Carraro, W. Denis, B. Gjoka, C. Zonta, K. Bartik, F. Cavani, S. Solmi, C. Bo, G. Licini, Adv. Synth. Catal .2018, 360, 3281–3291; DOI:10.1002/adsc.201800050 ).